Optimalisasi Sertifikasi Halal Untuk Umkm: Solusi Bagi Pasar Kamu Denai Lama Dalam Menjamin Kehalalan Produk - Tasya Maulida; Zuhrinal M. Nawawi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This article aims to analyze the importance of halal certification from the Indonesian Ulema Council (MUI) for Micro, Small, and Medium Enterprises (MSMEs) in the food sector, especially chicken-based products. The method used in this study is a qualitative approach to understand the challenges faced by MSMEs in obtaining halal certification, with a focus on the development of culinary tourism in Pasar Kamu, Denai Lama Village. The results of the study show that halal certification not only guarantees the halalness of products, but also improves quality, safety, and competitiveness in the market, as well as expanding the market share of MSMEs amid increasing awareness of Muslim consumers. Although 80% of traders in Pasar Kamu have obtained halal certificates, the main challenge faced is the lack of certified chicken slaughtering facilities, which hinders the other 20% of traders. Recommendations to overcome this obstacle include the provision of certified slaughtering facilities, assistance in the certification process, and cooperation with halal meat providers. Thus, halal certification is the key to increasing consumer confidence, product competitiveness, and village economic sustainability.